2012
DOI: 10.1002/jctb.3982
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of sulfide on the nitrifying respiratory process

Abstract: BACKGROUND: Biological wastewater treatment by nitrification is widely used; however information on inhibition of nitrification by sulfide is still scarce. The aim of this study was to evaluate the inhibitory effect of different initial sulfide concentrations on ammonium and nitrite oxidizing processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 28 publications
3
32
1
1
Order By: Relevance
“…found that the IC 50 of initial sulfide concentration on a mixing of attached and suspended nitrifying sludge was 13 mg L −1 . Bejarano et al . proposed IC 50 values of sulfide for ammonium and nitrite oxidation of 2.6 ± 0.3 and 1.2 ± 0.2 mg L −1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…found that the IC 50 of initial sulfide concentration on a mixing of attached and suspended nitrifying sludge was 13 mg L −1 . Bejarano et al . proposed IC 50 values of sulfide for ammonium and nitrite oxidation of 2.6 ± 0.3 and 1.2 ± 0.2 mg L −1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies are reported in the literature for inhibition of nitrification by toxic compounds, which include substrates of nitrifying biomass (free ammonia and free nitrite acid), salt, heavy metals, organic compounds, and inorganic anions . Owing to biomass acclimation, a constant low‐level exposure to toxic compounds usually shows insignificant adverse influences on microbial activity, but high concentration or shock loads of toxic compounds can lead to complete or partial failure of the nitrification process …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While recent studies have evaluated the impacts of sulfide on mixed culture nitrifying biomass, most of the studies were aimed to achieve partial nitrification by inhibiting NOB with sulfide (Erguder et al, 2008, Beristain-Cardoso et al, 2010, Kouba et al, 2017, Seuntjens et al, 2018). Some studies have demonstrated that AOB were partially inhibited and were more resilient to sulfide inhibition than NOB (Bejarano Ortiz et al, 2013, Kouba et al, 2017). However, the specific impact of biogas constituents on AOB mediated biomethanol production has not been evaluated and is as such warranted.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, H 2 S is toxic for the metabolism of many bacteria (Bejarano et al 2013;Zhou et al 2014).…”
Section: Introductionmentioning
confidence: 99%